Edukasi Pencegahan dan Penanganan Cedera Hamstring pada Pemain Sepak Bola di Komunitas Jambi Fun Soccer - Hadi, Putra; Faridah, Faridah (Jurnal Abdimas Kesehatan (JAK), 2024)
Hamstring injury is an injury to the hamstring muscle tissue due to direct or indirect damage from being stretched beyond normal limits. This injury often occurs in the groin muscles, hamstrings, and quadriceps muscles. Hamstring injuries often occur in altitudinarians usually in one of the hamstrings muscles that are torn or stretched due to trauma and sudden movement or Movement suddenly stops. The objective of this study is to increase knowledge about handling hamstring injuries in soccer players in the Jambi Fun Soccer community. Methods: this community service is in the form of delivering material and practicing directly with the help of leaflet and presentation media as well as simulation of injury management program exercises in the form of Stretching Exercise techniques or Stretching Exercises in the Hamstring area. After this counseling is done is the increased knowledge of soccer players about hamstring strain injuries and the importance of stretching exercise in handling sports injuries. This is indicated by the ability of the players to answer questions given after counseling. Conclusion: The positive response given by the players was very diverse and on average gave a very satisfied response to the implementation of this work program.